‘Splendid Little Soldiers’—Invasion, Empire and the Fantasy of Dominance in Saki’s When William Came - Petra Rau (Cahiers Victoriens et Edouardiens)
This essay is centrally concerned with the ambivalent politics of the last antebellum invasion novel, Saki’s When William Came (1913). Saki radically disrupts the English fantasy of dominance and imagines the end of the British Empire culminating not just in a German invasion but in a lasting occupation of England. In representing the Germans as admirable imperialists, Saki deconstructs national difference—the very criterion upon which both invasion fiction and imperialist politics are based. Therefore his dystopia is symptomatic of a wider crisis of Englishness as well as considerable imperial anxiety. Saki’s solutions to these contemporary fears endorse a muscular masculinity and a redemptive militarism in strong contrast to the homoerotic interests of his earlier years and works. Furthermore, the narrative contemplates three responses to occupation: retreat into conservative pastoralism, collaboration as indirect rule, and passive resistance. This inverted imperialist dynamic in fiction, however, has to engage with modes of resistance to British imperialism as they are beginning to manifest themselves in reality. This strategy undermines the imperialist ethos and its continuing fantasy of dominance upon which the novel’s outrageous dystopia is based, foreshadowing not just the contortions of WWI propaganda but the real end of the British Empire.